Порівняння енергоефективності струминних гомогенізаторів молока з роздільною подачею вершків - Самойчук, Кирило Олегович; Ковальов, Олександр Олександрович; Червоткіна, Олександра Олександрівна; Samoichuk, Kyryl; Kovalov, Oleksandr; Chervotkina, Oleksandra (Запоріжжя : ТДАТУ, 2023)
UA: В статті проведене порівняння енергоефективності струминного гомогенізатора молока та струминно-щілинного гомогенізатора, обидва з яких реалізують принцип роздільної подачі вершків. Отримані результати свідчать про високі значення потужності насосу подачі вершків, які перевищують відповідні показники насосу подачі знежиреного молока в 5,5–5,7 разів. В результаті проведеного аналізу визначено, що при однакових показниках продуктивності на рівні 1000 л/год потужність струминно-щілинного гомогенізатора молока майже в 1,5 рази менше за відповідний показник у струминному гомогенізаторі молока з роздільною подачею вершків. Аналіз мікрофотографій процесу свідчить про більш ефективне зменшення середнього діаметра жирових кульок при обробці в струминно- щілинному гомогенізаторі (0,82 мкм) в порівнянні з струминним гомогенізатором з роздільною подачею вершків (0,88мкм). EN: The results of the latest research indicate that it is possible to increase the energy efficiency of the process of dispersing the fat phase of a milk emulsion due to the implementation of the principle of separate feeding of cream. This principle was implemented taking into account the hypothesis of the dominant role in the process of the destruction of fat globules of the difference between the speeds of skimmed milk and cream in the two designs. The article compares the energy efficiency of a jet milk homogenizer and a jet-slot homogenizer, both of which implement the principle of separate cream feeding. The obtained results indicate high values of the power of the cream supply pump, which exceed the corresponding indicators of the skim milk supply pump by 5.5–5.7 times. As a result of the analysis, it was determined that with the same performance indicators at the level of 1000 l/h, the power of the jet-slit milk homogenizer is almost 1.5 times less than the corresponding indicator in the jet milk homogenizer with separate cream supply. The analysis of photomicrographs of the process shows a more effective reduction of the average diameter of fat balls during processing in a jet-slit homogenizer (0.82 μm) compared to a jet homogenizer with a separate supply of cream (0.88 μm). This fact is explained by the greater involvement of the adjacent liquid layers in the dispersion process, which leads to the intensification of the process and is associated with the use of an annular gap in the jet-slit homogenizer instead of cream supply channels. To increase the efficiency of dispersion in a jet milk homogenizer with separate cream supply, it is necessary to reduce the diameter of the cream supply channels, which will naturally lead to an increase in the required power of the drives.
Comparison of energy efficiency of stream milk homogenizers with separate cream supplyk
Самойчук К. О., Ковальов О. О., Червоткіна О. О. Порівняння енергоефективності струминних гомогенізаторів молока з роздільною подачею вершків. Науковий вісник Таврійського державного агротехнологічного університету : електронне наукове фахове видання. Запоріжжя : ТДАТУ. 2023. Вип. 13, том 2. C. 135-142.
Keywords: середній діаметр; струминний гомогенізатор; канал подачі; вершки; енергетичні витрати; молоко; порівняльна оцінка; methodology; parameters; annular gap; supply channel; cream; jet homogenizer; milk